(untitled) (Proceedings of International Educators Conference, 2023)
This article discusses the development of the marketing sector of companies in the Republic of Uzbekistan and the increase in the sales volume of their manufactured products, as well as the specific increase in the sales volume of the products manufactured in the Republic of Uzbekistan and the acceleration of their sales volume. The article also analyzes the development of manufactured products through proper marketing. Of course, through proper and targeted marketing, it is possible to achieve the sales volume of products in the Republic of Uzbekistan and their sales based on market demand.